Penentuan Lokasi Pabrik dalam Rencana untuk Perluasan Perusahaan (studi di PT 3M Indonesia dengan sistem Proses Hirarki Analitik) - Dzulfikri (Jurnal Aplikasi Manajemen, 2013)
The research aims to analyze the feasibility of the location by considering some criteria such ascost, location and risk from the land purchase project to choose the optimum location for manufacturingfacilities, warehouses, and a research and development that can support the growth of company up to 10years. Object of the research is determining the location of the factory in an industrial park close to thecenter of the automotive industry using the analytical hierarchy process (AHP) and sensitivity analysis.From internal analysis determined three criteria: 1) location, 2) Costs and 3) Risk. An additional 9subcriteria-1 and 35subcriteria-2 are used to make a clear judgment for respondents. After going throughthe initial land selection process then selected nine alternative plant sites in industrial park. From theanalysis using the AHP Expert Choice software found that the Location criteria has a major effect on thedecision making factor compare with Cost and Risk criteria, At the end from the 9 sites listed, AHP selectedthree most important alternative locations. However, after the sensitivity analysis conducted, the sequencesfrom the top 3 location are changed due to the sensitivity of the weighting cost criteria.